To solve the equation \(5(2x + 2) - 7x = 3x + 6\), let's start by simplifying each side.
-
Distribute \(5\) on the left side: \[ 5(2x + 2) = 10x + 10 \] So the equation becomes: \[ 10x + 10 - 7x = 3x + 6 \]
-
Combine like terms on the left side: \[ (10x - 7x) + 10 = 3x + 6 \] This simplifies to: \[ 3x + 10 = 3x + 6 \]
-
Now, subtract \(3x\) from both sides: \[ 10 = 6 \]
This outcome is a contradiction, meaning there are no values of \(x\) that will satisfy the equation. Therefore, the equation has no solution.
The final answer is: The equation has no solution.